Are apprenticeships beneficial in sub-Saharan Africa? - Francis Teal (IZA World of Labor, 2016)
Apprenticeships are the most common form of non-academic training in sub-Saharan Africa. Most apprenticeships are provided by the private sector, for a fee, and lead to self-employment rather than to wage jobs. Where the effects have been measured, they show that earnings are not higher, on average, for people who did an apprenticeship than for those who did not. This presents a conundrum. Why would people pay for apprenticeship training that does not benefit them? Research reveals that apprenticeships do benefit some people more than others. Especially striking is that the returns to apprenticeships can fall with the level of education.
Keywords: J24; J46; O17; O55; 330; apprenticeship; Africa; training; human capital